"Golet v údolí" Ivana Olbrachta i jego polskie tłumaczenie - Brzezina, Maria; Pösingerová, Kateřina (Stylistyka, 1998)
The authors compare the original Czech text (with linguistic Jewish and Ruthenian stylization) with its Polish translation by Z. Hierowski. They indicate several stylistic tendencies in the translation, e.g. the stylistical substitution (changing biblical proper names and Jewish appellatives to match Polish literary characters), the intensification of Jewish stylization or its neutralization. Thus, the local Hasidic-Ruthenian colour is partially lost.